2015
DOI: 10.1177/0022034515576051
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a/Ror2 Mediates Temporomandibular Joint Subchondral Bone Remodeling

Abstract: Increased subchondral trabecular bone turnover due to imbalanced bone-resorbing and bone-forming activities is a hallmark of osteoarthritis (OA). Wnt5a/Ror2 signaling, which can derive from bone marrow stromal cells (BMSCs), takes a role in modulating osteoblast and osteoclast formation. We showed previously that experimentally unilateral anterior crossbites (UACs) elicited OA-like lesions in mice temporomandibular joints (TMJs), displaying as subchondral trabecular bone loss. Herein, we tested the role of BMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 35 publications
3
39
0
Order By: Relevance
“…Based on a gene array analysis, Appleton et al indicated that the gene expression changes in a surgically developed rat OA model were similar to those found in human OA . Recently, we developed a prosthetic unilateral anterior crossbite (UAC) rodent model in which typical OA‐like lesions were observed in TMJs, such as chondrocyte death, cartilage matrix loss, osteochondral interface stiffening and abnormal reparative bone turnover . In the present study, we first detected molecular changes in the PBLs of UAC rats.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Based on a gene array analysis, Appleton et al indicated that the gene expression changes in a surgically developed rat OA model were similar to those found in human OA . Recently, we developed a prosthetic unilateral anterior crossbite (UAC) rodent model in which typical OA‐like lesions were observed in TMJs, such as chondrocyte death, cartilage matrix loss, osteochondral interface stiffening and abnormal reparative bone turnover . In the present study, we first detected molecular changes in the PBLs of UAC rats.…”
Section: Introductionsupporting
confidence: 57%
“…13 Recently, we developed a prosthetic unilateral anterior crossbite (UAC) rodent model in which typical OA-like lesions were observed in TMJs, such as chondrocyte death, cartilage matrix loss, osteochondral interface stiffening and abnormal reparative bone turnover. [14][15][16][17][18] In the present study, we first detected molecular changes in the PBLs of UAC rats. We then described the significance of the molecular changes disclosed in the PBLs of the UAC rats in the related tissues, including the alveolar bone, TMJ disc, mandibular condylar cartilage and subchondral bone.…”
Section: Backg Rou N Dmentioning
confidence: 92%
See 1 more Smart Citation
“…Wnt5a/Ror2 signaling in bone marrow stromal cells of the subchondral bone was enhanced in a surgically induced TMJ OA mouse model. Cxcl12 and Rankl gene expression induced by JNK and Ca 2+ /NFAT signaling pathways was increased, leading to activation of osteoclast differentiation and enhanced subchondral bone turnover [31]. …”
Section: Wnt/β-catenin Signaling In Tmj Oamentioning
confidence: 99%
“…Deletion of Adamts5 or double KO of both Adamts4 and Adamts5 prevented cartilage degradation in a surgically induced knee OA mouse model [55, 56]. In β-catenin overexpressing mice, β - catenin ( ex3 ) Col2CreER , expression of both Adamts4 and Adamts5 genes in disc tissues was upregulated [31]. These findings revealed that Mmp13 and Adamts4 / 5 are critical for cartilage erosion during progression, and pharmacologic inhibition of these enzymes may serve as an alternative strategy for osteoarthritis treatment.…”
Section: Chondrocyte β-Catenin Signaling In Cartilage Degeneration Anmentioning
confidence: 99%